HYBRID LEARNING AUTHENTIC ASSESSMENT: TEACHER PRACTICE AND CHALLENGE - Maulidah Furqoby; Alfan Hariri; Achmad Anang Darmawan (STKIP AL HIKMAH SURABAYA, 2024)
The changing of teaching learning process also changes the way how teachers assess their students. Therefore, online authentic assessment is considered more suitable for assessing students. This research is aimed to identify teacher’s way in implementing authentic assessments during online classroom and the challenges may be faced. This research used qualitative approach to find out the implementation of authentic assessment and the challenges during online learning by observing and interviewing the teacher. The study found out that teacher used performance assessment in assessing student’s speaking skill. The teacher did some steps in implementing authentic assessment, namely identify the standards, creating authentic task, giving evaluation, and doing assessment rubric. The study also found out some challenges, such as teacher was not able to control the student’s process of making the work, student’s limited time, and passive student.